Isolation, Identification Bacteria and Bioremediation of Soil Contaminate Crude Oil from Specific Area (Baiji_Iraq) - Hussein, Maha Hamdei; Saeed, Ibrahim Omar (Journal for Research in Applied Sciences and Biotechnology, 2022)
In this paper new eight types of bacteria that degrading crude oil were isolated. The isolated were from Baiji, near Tikrit, the center of Salah al-Din Governorate, IRAQ. The nucleotide sequences of the 16rRNA gene revealed that these isolates belong to the genus Bacillus, Cytobacillus and Staphylococcus. These isolated bacteria proved their ability to degradation petroleum hydrocarbons with varying effectiveness, as Cytobacillus firmus IBMA1 bacteria proved 98% effective in degrading hydrocarbons among the mineral salts in petroleum, Bacillus cereus IBMA3 showed a capacity to crack oil compounds by 92% in the medium of SMS mineral salts agar and Bacillus zhangzhouensis IBMA4 showed a cracking ability of 90% for the compounds present in crude oil. The other bacteria degraded petroleum compound with different rates. Based on it, three species that are big destroyers were taken to bioremediate crude oil containment soil from the same polluted site. The capacity of each basin is 10 kg. Each basin was treated with one type of bacteria over a period of two months. Then also, gas chromatography (GC) was used for soil samples after one and two months of treatment. The experiment was conducted from 17/2/2022 to 17/4/2022. The biological treatment was done using bacteria and contaminated soil. The results showed that IBMA1 bacteria have a great ability to consume PAHs with a consumption rate of 60.365% and that the lowest concentration of the remaining aromatic hydrocarbons was (6.5ppm), while IBMA3 bacteria showed their ability to consume PAHs with an average of 52.217% within two months. From the treatment, the lowest concentration of the remaining aromatic hydrocarbons was (9ppm) and IBMA4 bacteria showed the minimum ability to consume polycyclic aromatic hydrocarbons, with a consumption rate of 44.65% as an average consumption, and the lowest remaining concentrations of petroleum hydrocarbons were by (12ppm), while the average consumption of compounds during the two-month treatment period was 39.280%, and the results of the statistical analysis show the superiority of soil treatment with IBMA1 bacteria over IBMA3 bacteria and IBMA4 bacteria at the probability of P≤0.01.